ANALISISSOSIOLOGIEKONOMIKELEMBAGAAN DALAMTRANSFORMASISOSIOKULTURALMASYARAKATADAT (KasusSukuDuanodi ProvinsiRiau) - Viktor Amrifo (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
This paper was aimed (1) to analyze the institutional mechanism ofsocio-cultural transformation of Tribe Community, and (2) to analyze the socialmechanism of livelihood change of Duano Tribe. Instrumental case study wasconducted to Duano Tribe in Riau Province. Results showed that (1) the socio-cultural transformation process was pushed by the resettlement program for TribeCommunity in Indonesia, (2) sustainable livelihood role as incentive structure andAMAN as organizational field in the NIES frame analyses, and (3) the livelihoodstrategy of Duano household was maximizing the human capital of familymember. Economic behavior of Duano family member was oriented by (1) sharebelief, (2) socially constructed meaning about welfare and money, (3) the hope ofincentive structure, and (4) compliance to formal rules of Tribe CommunityResettlement Policy.Keywords: Socio-cultural Transformation, Sustainable Livelihood, LivelihoodChange, AMAN, Duano Tribe